# Heron’s Formula

Class :- IX C
ROLL NO. :- 24

• Who discovered heron’s formula? • Examples. .Contents :• What is heron’s formula ? • Discovery. • Proofs.

[1] gives the area of a triangle by  requiring no arbitrary choice of side as base or vertex as origin.What is heron’s formula? • In geometry.  contrary to other formulas for the area of a triangle. .  named after Hero of Alexandria. Heron's formula (sometimes called Hero's formula). such as half the  base times the height or half the norm of a cross product of two sides.

.

Heron’s formula gives the area ∆ of a triangle as ∆=√s(s-a) s(s-b) s(s-c) Heron’s formula may be stated beautifully using a Caley-Menger determinant as -16∆² = 0 a b c =0 1 1 1 a 0 b c =1 0 c² b² b c 0 a =1 c² 0 a² c b a 0 =1 b² a² 0 .• An important theorem in plane geometry.b and c and the semiperimeter S=½(a+b+c) Of a triangle. Given the lengths of the sides a. also known as Heron’s formula.

a² 1 -1 1 b² 1 1-1 c² .• Another highly symmetrical form is given by (4∆)² = [a² b² c²]. -1 1 1 .

Discovery :- A triangle with sides a. in geometry. heron’s formula (sometimes called Hero formula) is named after hero of Alexandria and states that the area of a triangle whose sides Have lengths a .b and c. b and c is a=√xYZ Y=(u-V+w)(V+w+u) b=√yZX y=(V-w+u)(w-u+V) c=√zXY Z=(v-W+u)(W+u+v) d=√xyz z=(W-u+v)(u-v+W) X=(w-U+v)(U+v+w) x=(U-v+w)(v-w+U) .

Who discovered Heron’s Formula? Archimedes discovered Heron’s formula. .

(16-15) =√576 =24 .Example:•  Let ∆ABC be the triangle with sides a=4. (16-4) . (16-13) .b=13 and c=15. and the área is  A=√s(s-a) (s-b) (s-c) =√16 . the  semiperimeter is S=½(a+b+c)=½(4+13+15)=16.

We'll modify the right hand side of the formula by noting that • p - a = (- a + b + c)/2. . Introduce the semiperimeter p = (a + b + c)/2 and the area S. we have S = ab/2. Then Heron's formula asserts that S2 = p(p - a)(p - b)(p - c) • For the right triangle with hypotenuse c.b and c. p - b = (a - b + c)/2. p - c = (a + b - c)/2.Proof :• Let the sides of a triangle have lengths a.

• It takes a little algebra to show that = (a + b + c) (- a + b + c) 16S2 (a - b + c) (a + b - c) = 2a2b2 +   2a2c2 + 2b2c2 4 4 4 )2 2 2 2(a 2  + b 2  + c 2 For the right triangle. 4a b = 2a b  + 2a2c2 + 2b2c2 .(a4 + b4 + c4)So we have Taking all terms to the left side and grouping them yields (a4 + 2a2b2 + b4) .2a2c2 .2b2c2 + c4 = 0 . 16S  = 4a b .

• (a2 + b2)2[(a2 + b2) - c2]2 = 0 And Finally. 2c2(a2 + b2) + c4 =0 THANKYOU .